1993
DOI: 10.1002/hc.520040510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Te‐alkyl carbamotelluroates from tellurium, carbon monoxide, amines, and alkyl halides

Abstract: Lithium amides reacted with tellurium under atmospheric pressure of carbon monoxide to yield lithium carbamotelluroates which were trapped with alkyl halides to give Te-alkyl carbamotelluroates in good yields. Results of control experiments suggested that lithium carbamotelluroates were formed by the reaction of tellurium with carbamoyllithiums generated in situ from lithium amides and carbon monoxide. It was revealed also that yields were imprwed when tellurium was preliminarily treated with Iithium amides pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Since we already developed tellurium-assisted carbonylation and imidoylation of amines with carbon monoxide and isocyanides, respectively, starting from lithium amides, we examined the reaction using lithium amides instead of amines. Lithium piperidide, generated from piperidine and n -BuLi in the presence of HMPA at −78 °C, was allowed to react with tellurium and then isocyanide 2 and CuI (5 mol %) were added at room temperature.…”
mentioning
confidence: 99%
“…Since we already developed tellurium-assisted carbonylation and imidoylation of amines with carbon monoxide and isocyanides, respectively, starting from lithium amides, we examined the reaction using lithium amides instead of amines. Lithium piperidide, generated from piperidine and n -BuLi in the presence of HMPA at −78 °C, was allowed to react with tellurium and then isocyanide 2 and CuI (5 mol %) were added at room temperature.…”
mentioning
confidence: 99%
“…Bis( N,N ‐dimethylcarbamoyl) ditelluride ( 1 ) was at first prepared in moderate yield by treating N,N ‐dimethylformamide (DMF) with sodium and elemental tellurium under heating followed by aerobic oxidation of the reaction mixture . Preparation of bis( N,N ‐diethylcarbamoyl) ditelluride ( 2 , R 1 = C 2 H 5 ) was also carried out by treating N,N ‐diethylformamide (DEF) with lithium metal and elemental tellurium through a similar procedure as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…However, only limited research works on generation, trapping, or metal complexation of telluroaldehydes B were reported due to the high instability of the target species toward air, light, and heating, as well as the lack of preparative methods of suitable and easily accessible precursors. In the course of our studies on the novel generation of higher‐row chalcogenocarbonyl compounds, we previously reported a convenient preparation of stable ditelluroacetal derivatives A through the reaction of in situ generated tellurocarbamate ions with gem‐dihaloalkanes . Actually, such ditelluroacetals A are recognized as potent precursors for telluroaldehydes B in the light of their symmetrical structures with an easily removable electron‐withdrawing carbamoyl group on each tellurium atom, and compouds A are expected to undergo SnCl 4 ‐induced unsymmetrical C–Te bond cleavage to generate telluroaldehydes B through push–pull type removal of N,N ‐diethyltellurocarbamate in an analogous manner of our previous report on the generation of selenoaldehydes from bis( N,N ‐dimethylcarbamoylseleno)methanes .…”
Section: Introductionmentioning
confidence: 99%
“…Kambe et al found that isocyanate can react with i Bu 2 AlTeR to give tellurocarbamate after hydrolysis (Figure d) . Sonoda et al reported that lithium amides reacted with tellurium under atmospheric pressure of carbon monoxide to yield lithium carbamotelluroates which reacted with alkyl halides to give Te-alkyl tellurocarbamates (Figure e) . These methods generally require multiple steps and use of active organometallic reagents and suffer from limited scope.…”
mentioning
confidence: 99%